An in vivo BSL-2 model for henipavirus infection based on bioluminescence imaging of recombinant Cedar virus replication in mice - Huaman, Celeste; Clouse, Caitlyn; Rader, Madeline; Yan, Lianying; Bai, Shuangyi; Gunn, Bronwyn M.; Amaya, Moushimi; Laing, Eric D.; Broder, Christopher C.; Schaefer, Brian C. (Frontiers in Chemical Biology, 2024)
Henipaviruses are enveloped single-stranded, negative-sense RNA viruses of the paramyxovirus family. Two henipaviruses, Nipah virus and Hendra virus, cause a systemic respiratory and/or neurological disease in humans and ten additional species of mammals, with a high fatality rate. Because of their highly pathogenic nature, Nipah virus and Hendra virus are categorized as BSL-4 pathogens, which limits the number and scope of translational research studies on these important human pathogens. To begin to address this limitation, we are developing a BSL-2 model of authentic henipavirus infection in mice, using the non-pathogenic henipavirus, Cedar virus. Notably, wild-type mice are highly resistant to Hendra virus and Nipah virus infection. However, previous work has shown that mice lacking expression of the type I interferon receptor (IFNAR-KO mice) are susceptible to both viruses. Here, we show that luciferase-expressing recombinant Cedar virus (rCedV-luc) is also able to replicate and establish a transient infection in IFNAR-KO mice, but not in wild-type mice. Using longitudinal bioluminescence imaging (BLI) of luciferase expression, we detected rCedV-luc replication as early as 10 h post-infection. Viral replication peaks between days 1 and 3 post-infection, and declines to levels undetectable by bioluminescence imaging by 7 days post-infection. Immunohistochemistry is consistent with viral infection and replication in endothelial cells and other non-immune cell types within tissue parenchyma. Serology analyses demonstrate significant IgG responses to the Cedar virus surface glycoprotein with potent neutralizing activity in IFNAR-KO mice, whereas antibody responses in wild-type animals were non-significant. Overall, these data suggest that rCedV-luc infection of IFNAR-KO mice represents a viable platform for the study of in vivo henipavirus replication, anti-henipavirus host responses and henipavirus-directed therapeutics.